2022
DOI: 10.13075/mp.5893.01203
|View full text |Cite
|
Sign up to set email alerts
|

A study of character strengths, work engagement and subjective well-being in Chinese registered nurses

Abstract: Background: Nurses displayed low levels of subjective well-being and high turnover intention. How to enhance the subjective well-being and decrease the turnover rate of nurses is of great importance. However, little is known about whether work engagement mediates between character strengths and subjective well-being. The study aims to explore character strengths, work engagement and subjective well-being in nurses, and to determine whether work engagement plays a mediating role between the relationship. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The results also showed that work engagement positively affected all three sub-domains of well-being, that is, emotional, social, and psychological well-being increased when nurses were engaged in their work. Studies with similar findings [ 16 , 17 , 28 , 29 ] observed that increased work engagement led to well-being. Tomieeto et al [ 33 ] found that the impact of sub-domains of work engagement on nurses’ well-being differed according to the age of the nurse.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The results also showed that work engagement positively affected all three sub-domains of well-being, that is, emotional, social, and psychological well-being increased when nurses were engaged in their work. Studies with similar findings [ 16 , 17 , 28 , 29 ] observed that increased work engagement led to well-being. Tomieeto et al [ 33 ] found that the impact of sub-domains of work engagement on nurses’ well-being differed according to the age of the nurse.…”
Section: Discussionmentioning
confidence: 62%
“…Work engagement, being active and vigorous, reflects the qualities of vital workability and professional identity, which involves dedication (loving work and a sense of honor), vigor (high vitality and resilience at work), and absorption (dedication to work and reluctancy to put work aside) [ 16 ]. Further, Ding et al have revealed that work engagement is crucial to achieving nurses’ subjective well-being [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Kim et al [31] showed that teachers with stronger character strengths have lower probabilities of work burnout, leading to more positive attitudes toward their organization and reduced intentions to resign. Furthermore, Costantini et al [24], Bakker et al [32], and Ding et al [33] found that higher character strength levels can effectively increase work engagement and dedication, psychological attachment to the organization, and willingness to stay.…”
Section: Relationship Between Character Strengths and Turnover Intentionmentioning
confidence: 99%